Upaya Meningkatkan Kemampuan Menyusun Rencana Pelaksanaan Pembelajaran melalui Bimbingan Berkelanjutan bagi Guru Agama di MTs Wilayah Binaan Bantul - Ening Yuni Soleh Astuti (Jurnal Pendidikan Madrasah, 2019)
Education Unit Level Curriculum (KTSP) or 2013 curriculum which is arranged by the Madrasah, is one of the devices that should be composed/made by the teacher of the subjects is the Learning Plan (RPP). But in fact the teacher uses RPP that is obtained from the forum MGMP and copypaste from other sources without any changes/adjustments to the situation and condition of the madrasah. One of the reason is the low ability of teachers in drafting RPP. The research aims to improve the teacher's ability to compile RPP-compliant standards through ongoing mentoring. The subject of this research is the teacher of PAI target area in Bantul Regency, semester I, school year 2019/2010. The research method used is school action research/MADRASAH with 2 (two) cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. The data collection uses observation/observation methods. From the processing and analysis of data was found that ongoing coaching activities can improve the teacher's ability to compile RPP, proven average teachers ' ability score in the initial conditions (before the lead) was 53.24, on Cycle 1 to 80.62; And in Cycle 2 to 90.22. Upgrading from initial conditions to a final state of 69.45% is a major improvement and it is advisable to use sustainable mentoring to improve the teacher's ability to compile RPP.